2014
DOI: 10.1007/s00232-014-9727-z
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin and N-Arachidonoyl-dopamine (NADA) Decrease Tension by Activating Both Cannabinoid and Vanilloid Receptors in Fast Skeletal Muscle Fibers of the Frog

Abstract: Previous studies have indicated that vanilloid receptor (VR1) mRNA is expressed in muscle fibers. In this study, we evaluated the functional effects of VR1 activation. We measured caffeine-induced contractions in bundles of the extensor digitorum longus muscle of Rana pipiens. Isometric tension measurements showed that two VR1 agonists, capsaicin (CAP) and N-arachidonoyl-dopamine (NADA), reduced muscle peak tension to 57 ± 4 % and 71 ± 3% of control, respectively. The effect of CAP was partially blocked by a V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Additionally, the sexes have shown different predispositions to developing kidney injury due to diabetes [37]. Moreover, as mentioned above, previous studies have provided evidence that CAPS was capable of stimulating receptors other than TRPV1, like CB1 receptors [8], which were reported to be overexpressed in DN kidneys. Therefore, in future studies, we plan to use both sexes of rats when examining the CAPS effect together with an antagonist of the CB1 receptor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the sexes have shown different predispositions to developing kidney injury due to diabetes [37]. Moreover, as mentioned above, previous studies have provided evidence that CAPS was capable of stimulating receptors other than TRPV1, like CB1 receptors [8], which were reported to be overexpressed in DN kidneys. Therefore, in future studies, we plan to use both sexes of rats when examining the CAPS effect together with an antagonist of the CB1 receptor.…”
Section: Resultsmentioning
confidence: 99%
“…CAPS treatment also reduced the expression of inflammation markers and oxidative stress [7]. However, it was recently reported that CAPS could also activate cannabinoid brain type 1 (CB1) receptors [8]. CB1 receptors were reported to be expressed in podocytes [9].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on the impact of the pharmacological modulation of TRPV1 on muscle function is barely more abundant. Only one study revealed that pharmacological activation of TRPV1 by capsaicin decreases the tension of fast muscles in frogs [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oláh et al (2016) found that activation of the CB 1 ‐Gα protein pathway induces muscle fatigability that can be (partly) explained by a decrease in Ca 2+ sensitivity and a lower RyR‐mediated Ca 2+ release (Oláh et al, 2016). Accordingly, CB 1 agonism reduced the maximum tension of contractions in frog muscle fibers, induced by caffeine, which is known to induce Ca 2+ release from the sarcoplasmic reticulum (Huerta et al, 2009; M. G. Klein et al, 1990; Trujillo et al, 2015). Besides Ca 2+ , also Na + can be modulated by cannabinoid signaling to orchestrate muscle excitability.…”
Section: Cannabinoid System and Muscle Homeostasis: Paths And Challengesmentioning
confidence: 99%